The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1021/je4010799
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Efficiency of 2-[(1-Aza-15-crown-5)-1-ylmethyl)]-4-(phenyldiazenyl)-naphthalen-1-ol in the Liquid Extraction of Light Lanthanoid(III) Ions with 4-Benzoyl-3-phenyl-5-isoxazolone: The Role of Aza-Crown and Azo-Dye Fragments on the Extraction Ability

Abstract: The solvent extraction of light lanthanoids with a mixture of 4-benzoyl-3-phenyl-5-isoxazolone (HPBI) and an azo-dye containing aza-crown in the side chain as a synergist (S), 2-[(1-aza-15-crown-5)-1-ylmethyl)]-4-(phenyldiazenyl)-naphthalen-1-ol (PDN1A15C5), was studied. To examine the role of the azo-dye on the extraction ability, its simplified analogue 1-benzyl-1-aza-15-crown-5 (BA15C5) was applied. The influence of the nitrogen on the crown fragment was estimated by a comparison with the efficiency of a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Atanassova et al have already demonstrated that the extraction of Ln ions using the strongly coordinating compound HPBI in a set of molecular diluents proceeds through a proton-exchange reaction, forming neutral tris complexes. [23][24][25][26][27] The extraction mechanism and the extraction constant of the neutral tris complexes (Kex,3) were represented by the following equations:…”
Section: Mechanism Of Lanthanoids Extraction Using 4-benzoyl-3-phenylmentioning
confidence: 99%
See 2 more Smart Citations
“…Atanassova et al have already demonstrated that the extraction of Ln ions using the strongly coordinating compound HPBI in a set of molecular diluents proceeds through a proton-exchange reaction, forming neutral tris complexes. [23][24][25][26][27] The extraction mechanism and the extraction constant of the neutral tris complexes (Kex,3) were represented by the following equations:…”
Section: Mechanism Of Lanthanoids Extraction Using 4-benzoyl-3-phenylmentioning
confidence: 99%
“…(11) from slope analysis (data not shown in the figures). [23][24][25][26][27] In addition, the values of log Kex,3 for La 3+ , Eu 3+ , and Lu 3+ in the chloroform system were determined to be -1.34 ± 0.10, 0.85 ± 0.11, and 0.73 ± 0.10 by a linear leastsquares fitting of the plots, respectively. Electroneutrality is an essential principle, as only neutral complexes may enter the hydrophobic molecular layer.…”
Section: Mechanism Of Lanthanoids Extraction Using 4-benzoyl-3-phenylmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, combined with 4-benzoyl-3-phenyl-5-isoxazolone (HPBI), the synergistic extraction D values of 15-crown-5 (15C5), benzo-15-crown-5 (B15C5, Figure S1 ), 1-benzyl-1-aza-15-crown-5 (BA15C5, Figure S1 ), and 2-[(1-aza-15-crown-5)-1-ylmethyl)]-4-(phenyldiazenyl)-naphthalen-1-ol (PDN1A15C5, Figure S1 ) for Eu(III) ions are 1.0, 0.5, 2.5, and 6.3 at pH 2.4, respectively. 29 Specifically, the La(III), Pr(III), and Eu(III) ions are extracted as Ln(PBI) 3 ·2S complexes (S = PDN1A15C5), while the light lanthanoid(III) ions of the 4f-series (La–Gd) form the extraction complex as Ln(PBI) 3 ·S species (S = B15C5 and 15C5). It should be noted that the addition of crown ether increases the extraction efficiency and the separation factors between the heavier Ln(III) and light Ln(III) are higher than those found for their extraction with the extractant alone.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the effects of macrocyclic crown ether compounds on the extraction and separation of trivalent lanthanides/actinides, some extractants and synergistic agents derived from crown ethers were developed. For example, combined with 4-benzoyl-3-phenyl-5-isoxazolone (HPBI), the synergistic extraction D values of 15-crown-5 (15C5), benzo-15-crown-5 (B15C5, Figure S1), 1-benzyl-1-aza-15-crown-5 (BA15C5, Figure S1), and 2-[(1-aza-15-crown-5)-1-ylmethyl)]-4-(phenyldiazenyl)-naphthalen-1-ol (PDN1A15C5, Figure S1) for Eu­(III) ions are 1.0, 0.5, 2.5, and 6.3 at pH 2.4, respectively . Specifically, the La­(III), Pr­(III), and Eu­(III) ions are extracted as Ln­(PBI) 3 ·2S complexes (S = PDN1A15C5), while the light lanthanoid­(III) ions of the 4f-series (La–Gd) form the extraction complex as Ln­(PBI) 3 ·S species (S = B15C5 and 15C5).…”
Section: Introductionmentioning
confidence: 99%